PRODUCTION OF NANO EMULSION TERPOLYMERS BINDERS FOR TEXTILE APPLICATION - El Sheikh, M.M.M.; Hussein, A.I.; Meligi, G.A. (Acta Scientiae et Intellectus, 2024)
Micro emulsion polymer with a high content of ethyl acrylate soft monomer was the most used binder for textile pigment printing application. This work aimed to improve the physical and mechanical properties of pigment printing application using series of terpolymer prepared by polymerization of ethyl acrylate with methyl methacrylate and 2-ethyl hexyl acrylate at different concentration ratios of methyl methacrylate (2.5%, 5%, 7.5%, and 10%) respectively of the total monomer concentrations. The prepared terpolymers were characterized using solid content, molecular weight, coagulum, viscosity, drying time, UV, MFFT and TEM. The mechanical properties of the prepared polymers would be also examined. It was found that methyl methacrylate/ 2-ethyl hexyl acrylate/ethyl acrylate terpolymer of ratio (10:10:80) respectively showed the best heat fastness, mechanical fastness, soft handling and high color yield of pigment printed textile.